An electron microscopic study of neocortex of Syrian hamsters (Mesocricetus auratus) infected with SARS-CoV-2 (Coronaviridae: Coronavirinae: Betacoronavirus: Sarbecovirus) - Natal’ya M. Paramonova; Sergey V. Chepur; Mariya О. Pervak; Vadim A. Myasnikov; Mikhail A. Tyunin; Nikita S. Ilinskiy; Boris A. Kanevskij; Anna V. Smirnova (Вопросы вирусологии, 2022)
Introduction. Convalescent COVID-19 patients have various signs of central nervous system damage, including those directly associated with SARS-CoV-2. Hence, studies of SARS-COV-2 related morphological changes in neocortex are particularly relevant for understanding the mechanisms of their formation and development of approaches to preclinical evaluation of the effectiveness of antiviral drugs.